2020
DOI: 10.22159/ijap.2020v12i5.38762
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Drug Delivery System: Challenges and Approaches

Abstract: The ocular drug delivery deviates through a number of anatomical and physiological barriers, which have been a bottleneck for the ophthalmologists. The ocular barriers, static and dynamic, decrease the absorption of the therapeutic agents and the entry of the xenobiotics. Thus, a conventional ocular dosage form has various disadvantages of its use in ocular diseases. Hence, an ideal ocular delivery system has always been aimed, where the bioavailability of a drug is maintained for a longer period of time. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…These authors suggested that the dendrimer improved the drug efficacy by enhancing cellular delivery compared to pure ibuprofen. In ocular drug delivery, dendrimers are an ideal carrier system due to nonirritating, biocompatible, sterile, isotonic, and biodegradable properties (Raj et al, 2020). Viewed in this way, Vandamme and Brobeck (2005) improved the bioavailability of the pilocarpine increasing the resident time in the eye of the drug by using PAMAM dendrimers.…”
Section: Dendrimersmentioning
confidence: 99%
“…These authors suggested that the dendrimer improved the drug efficacy by enhancing cellular delivery compared to pure ibuprofen. In ocular drug delivery, dendrimers are an ideal carrier system due to nonirritating, biocompatible, sterile, isotonic, and biodegradable properties (Raj et al, 2020). Viewed in this way, Vandamme and Brobeck (2005) improved the bioavailability of the pilocarpine increasing the resident time in the eye of the drug by using PAMAM dendrimers.…”
Section: Dendrimersmentioning
confidence: 99%
“…Nanotechnology-based ophthalmic formulations fall into two broad categories: organic nanoparticles (liposomes, niosomes/discosomes, dendrimers, nanoemulsions, nanosuspensions, and nanospheres) and inorganic nanoparticles (metallic, carbonous, and silica nanoparticles and quantum dots). 5 , 27 , 29 Organic nanoparticles are essential carriers of pharmaceutical compounds, while inorganic nanoparticles have garnered significant attention for their theranostic properties. Despite, mesoporous silica inorganic nanoparticles are capable of absorbing exceptionally copious amounts of active substance inside their pores.…”
Section: Nanotechnology-based Formulationsmentioning
confidence: 99%
“…The active substance is released in a sustained manner which leads to enhanced bioavailability. 5 , 46 A natural polymer, chitosan, is often supplemented in ophthalmic formulations due to its endogenous mucoadhesive nature. Its positively charged amino groups interact with the negatively charged layer of the tear-film mucinous layer.…”
Section: In Situ -Forming Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discosomes were shown entrapping water-soluble solutes. Discosomes of 5(6)-carboxy-fluorescein were developed and started in retaining 50% of entrapped CF over a 24 h period at room temperature [52,53]. Discosomes are voluminous discoidal structures that subsist under definite conditions of this phase of non-ionic surfactant vesicle formation.…”
Section: Mechanism Of Action Of Discosomesmentioning
confidence: 99%